Fat Tail Analysis on S&P 100 Stocks-before and after US President Election - Thakur, Sandeep (Ushus Journal of Business Management, 2021)
The main aim of this paper is to determine whether the volatility in the stocks can be created by events like the US Election and whether it leads to Fat Tail in the stocks. Fat Tail analysis is a key factor in determining volatility and has been used in the economy as well as in many other fields like climate and health. Log return has been used to determine the Fat Tail. To make the work more reliable, two Presidential election periods, that of Barack Obama and Donald Trump is selected and is compared for volatility and Fat Tail. For this study, stocks from the S&P 100 are selected and observed. The results show that the US economy is not at all driven by who comes in power and when but rather by the present economic condition. Stocks showing heavy tails during the Obama presidency are primarily because the economy was under Sub Prime Crisis too.